Extra-Hepatic Biliary Atresia in Association with Polysplenia and Intestinal Malrotation - Jaishri Ramji; Rakesh S Joshi; Mitesh Bachani; Dungarsingh Rathore (EL-Med-Pub, 2013)
The syndromic form of biliary atresia accounts for 10-25% and is associated with a poor prognosis due to associated anomalies. We report a case of extrahepatic biliary atresia and polysplenia syndrome with jaundice since 19th day of life and who had undergone surgical correction of malrotation in the neonatal period. Inspite of successful Kasai's portoenterostomy at 52nd day of life, the child succumbed to post-operative sepsis.